Peripartum cardiomyopathy and dilated cardiomyopathy: different at heart - Bollen, Ilse A. E.; Van Deel, Elza D.; Kuster, Diederik W. D.; Van Der Velden, Jolanda (Frontiers in Physiology, 2015)
Peripartum cardiomyopathy (PPCM) is a severe cardiac disease occurring in the last month of pregnancy or in the first 5 months after delivery and shows many similar clinical characteristics as dilated cardiomyopathy (DCM) such as ventricle dilation and systolic dysfunction. While PPCM was believed to be DCM triggered by pregnancy, more and more studies show important differences between these diseases. While it is likely they share part of their pathogenesis such as increased oxidative stress and an impaired microvasculature, discrepancies seen in disease progression and outcome indicate there must be differences in pathogenesis as well. In this review, we compared studies in DCM and PPCM to search for overlapping and deviating disease etiology, pathogenesis and outcome in order to understand why these cardiomyopathies share similar clinical features but have different underlying pathologies.